A search-theoretic model of the term premium - Athanasios Geromichalos; Lucas Herrenbrueck; Kevin Salyer (University of California, Department of Economics, 2013)
A consistent empirical feature of bond yields is that term premia are, on average, positive. That is, investors in long term bonds receive higher returns than investors in similar (i.e. same default risk) shorter maturity bonds over the same holding period. The majority of theoretical explanations for this observation have viewed the term premia through the lens of the consumption based capital asset pricing model. In contrast, we harken to an older empirical literature which attributes the term premium to the idea that short maturity bonds are inherently more liquid. The goal of this paper is to provide a theoretical justification of this concept. To that end, we employ a model in the tradition of modern monetary theory extended to include assets of different maturities. Short term assets always mature in time to take advantage of random consumption opportunities. Long term assets do not, but agents may liquidate them in a secondary asset market, characterized by search-and-bargaining frictions a la Duffie, Garleanu, and Pedersen (2005). In equilibrium, long term assets have higher rates of return to compensate agents for their relative lack of liquidity. Consistent with empirical findings, our model predicts a steeper yield curve for assets that trade in less liquid secondary markets.
Keywords: E31; E43; E52; G12; 330; monetary-search models; liquidity; over-the-counter markets; yield curve